Topological Nanophotonics: Cavity Quantum Electrodynamics with Second‐Order Topological Corner State (Laser Photonics Rev. 14(8)/2020). Issue 8 (13th August 2020) - Xie, Xin; Zhang, Weixuan; He, Xiaowu; Wu, Shiyao; Dang, Jianchen; Peng, Kai; Song, Feilong; Yang, Longlong; Ni, Haiqiao; Niu, Zhichuan; Wang, Can; Jin, Kuijuan; et al.
Abstract : In article number 1900425 by Xiulai Xu, Xiangdong Zhang, and co‐workers, weak coupling between single quantum dot and the second‐order topological corner state is demonstrated, with enhancement of photoluminescence intensity and emission rate. This work provides a new platform to develop the topological nanophotonic circuitry for the manipulation of photons in classical and quantum regimes.